Women of the Harlem renaissance - Wall, Cheryl A. (Indiana University Press, 1995)
Features chapters on Jessie Redmon Fauset, Zora Neale Hurston and Nella Larsen. Also discusses other artists including Josephine Baker, Gwendolyn Bennett, Georgia Douglas Johnson, Charlotte Mason, Bessie Smith, Anne Spencer, and Jean Toomer.
Keywords: Fauset, Jessie Redmon -- Criticism and interpretation.; Hurston, Zora Neale -- Criticism and interpretation.; Larsen, Nella -- Criticism and interpretation.; Fauset, Jessie Redmon -- Critique et interprétation.; Hurston, Zora Neale -- Critique et interprétation.; Larsen, Nella -- Critique et interprétation.; Fauset, Jessie Redmon; Hurston, Zora Neale; Larsen, Nella; Fauset, Jessie Redmon -- Criticism and interpretation; Hurston, Zora Neale -- Criticism and interpretation; American literature -- African American authors -- History and criticism.; Women and literature -- United States -- History -- 20th century.; American literature -- Women authors -- History and criticism.; American literature -- 20th century -- History and criticism.; African American women -- New York (State) -- New York -- Intellectual life.; Harlem (New York, N.Y.) -- Intellectual life.; African Americans in literature.; Harlem Renaissance.; Littérature américaine -- Auteurs noirs américains -- Histoire et critique.; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Littérature américaine -- 20e siècle -- Histoire et critique.; Noires américaines -- New York (État) -- New York -- Vie intellectuelle.; Noirs américains dans la littérature.; Écrits de femmes américains -- Histoire et critique.; Harlem (New York, N.Y.) -- Vie intellectuelle.; LITERARY CRITICISM -- American -- General.; African American women -- Intellectual life; African Americans in literature; American literature; American literature -- African American authors; American literature -- Women authors; Harlem Renaissance; Intellectual life; Women and literature; New York (State) -- New York; New York (State) -- New York -- Harlem; United States; Schriftstellerin; Harlem renaissance; Frau; USA; Amerikaans.; Vrouwelijke auteurs.; Letterkunde.; American literature -- African American authors -- History and criticism; American literature -- Women authors -- 20th century -- History and criticism; American literature -- 20th century -- History and criticism; African American women -- New York.; Harlem (New York, N.Y.) -- Intellectual life; 1900-1999; African American women -- Intellectual life -- New York (State) -- New York; African American women in literature; American literature -- History and criticism -- 20th century; American literature -- Women authors -- History and criticism; Larsen, Nella -- Criticism and interpretation; Women and literature -- History -- 20th century -- United States; Criticism, interpretation, etc.; History